Quantification of Myocardial Dosimetry and Glucose Metabolism Using a 17-Segment Model of the Left Ventricle in Esophageal Cancer Patients Receiving Radiotherapy - Xua Sha; Guanzhong Gong; Chunlei Han; Qingtao Qiu; Yong Yin (FRONTIERS MEDIA SA, 2022)
Objective Previous studies have shown that increased cardiac uptake of(18)F-fluorodeoxyglucose (FDG) on positron emission tomography (PET) may be an indicator of myocardial injury after radiotherapy (RT). The primary objective of this study was to quantify cardiac subvolume dosimetry and(18)F-FDG uptake on oncologic PET using a 17-segment model of the left ventricle (LV) and to identify dose limits related to changes in cardiac(18)F-FDG uptake after RT. Methods Twenty-four esophageal cancer (EC) patients who underwent consecutive oncologic(18)F-FDG PET/CT scans at baseline and post-RT were enrolled in this study. The radiation dose and the(18)F-FDG uptake were quantitatively analyzed based on a 17-segment model. The(18)F-FDG uptake and doses to the basal, middle and apical regions, and the changes in the(18)F-FDG uptake for different dose ranges were analyzed.
Results A heterogeneous dose distribution was observed, and the basal region received a higher median mean dose (18.36 Gy) than the middle and apical regions (5.30 and 2.21 Gy, respectively). Segments 1, 2, 3, and 4 received the highest doses, all of which were greater than 10 Gy. Three patterns were observed for the myocardial(18)F-FDG uptake in relation to the radiation dose before and after RT: an increase (5 patients), a decrease (13 patients), and no change (6 patients). In a pairing analysis, the(18)F-FDG uptake after RT decreased by 28.93 and 12.12% in the low-dose segments (0-10 Gy and 10-20 Gy, respectively) and increased by 7.24% in the high-dose segments (20-30 Gy). Conclusion The RT dose varies substantially within LV segments in patients receiving thoracic EC RT. Increased(18)F-FDG uptake in the myocardium after RT was observed for doses above 20 Gy.